Cereal production practices and technical efficiency among farm households in major "teff" growing mixed farming areas of Ethiopia: A stochastic meta-frontier approach - Fisseha Zegeye Birhanu; Abrham Seyoum Tsehay; Dawit Alemu Bimerew (Cogent Economics & Finance, 2022)
This study examined the effects of research-based recommended cereal production practices on the technical efficiency of farm households based on household-level data generated from questionnaire surveys, focus group discussions, and key informant interviews. The technical efficiency scores were estimated using the stochastic meta-frontier approach because it allows addressing the expected differences in production technologies. Tobit regression framework was applied to identify factors related to farm inefficiency. Results showed mean technical efficiency of 58%, implying that the farm households can improve cereal output by about 36% with the current level of input mix and technologies. The t-test results revealed farm households who adopted high-yielding varieties with research-based recommended production practices were technically more efficient than their counterparts. Our econometric model results also indicated that the use of high-yielding varieties and research-based recommended seed rate affects the technical efficiency of farm households positively and significantly. In addition, we find gender, age, mobile telephone ownership, cooperative membership, access to input market, and crop damage as significant factors affecting the efficiency of farm households. Our findings highlight the importance of addressing technology adoption gaps and gender-based disparities, expanding access to information and modern inputs, strengthening social capital, and adopting climate change adaptation practices to improve the efficiency of farm households.
Keywords: G30; G32; G11; 330; Research recommended production practices; technical efficiency; metafrontier; cereal production; Ethiopia